Acute Anisakiasis at the Esophagogastric Junction Mimicking Angina Pectoris - Dong Chan Joo; Gwang Ha Kim; Moon Won Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Anisakiasis is a fish-borne zoonotic disease caused in humans by the ingestion of raw or undercooked seafood infected by anisakid larvae. Anisakiasis usually causes abdominal pain, nausea, and vomiting. However, other symptoms, including dysphagia, heartburn, and chest pain, are rare. A 55-year-old woman presented to the emergency department for the evaluation of sudden-onset chest pain. The findings of the cardiology work-up were all normal. Upper gastrointestinal endoscopy revealed a nematode at the esophagogastric junction, which was successfully removed. The chest pain immediately subsided thereafter. Herein, we report a rare case of anisakiasis at the esophagogastric junction, which caused chest pain mimicking angina pectoris and was treated with endoscopic removal.